Kreativitas Iklan Indomie di Televisi dari Masa ke Masa (Tahun 1980-2000an) - Margaret Margaret; Gregorius Genep Sukendro (Kiwari, 2022)
Advertising creativity is advertising that is original, there is creative thinking and innovation. The purpose of this study is to find out the beginning of Indomie advertising on television in terms of creativity from the first time the advertisement was made until now and find out how the implementation of Indomie product advertising by PT.Indofood. This study raises the issue of Indomie's advertising creativity, Indomie is an instant noodle product that has existed since 1980. The theory and research concepts used are advertising, advertising appeal, television media in mass communication, products, brands, and also creativity. This study use qualitative research with case study method. Data collection uses interviews with Raditya Cahya Buana as Quality Control Noodle and Television Advertising at PT. Indofood Semarang, document studies and literature studies. The conclusion of the research on Indomie advertising creativity is to display Indomie advertisements on television in an attractive way and present new Indomie products. Indonesian advertisements must be more flexible in determining the style of advertising so that consumers are interested in viewing and advertising acts as a medium of communication between producers and consumers, as an attractive product promotion media. Kreativitas iklan adalah iklan yang bersifat originalitas, terdapat pemikiran yang kreatif dan juga inovasi. Tujuan penelitian ini adalah untuk mengetahui awal iklan Indomie di televisi dari segi kreativitasnya dari pertama kali dibuat iklan sampai sekarang dan mengetahui bagaimana pelaksanaan periklanan produk Indomie yang dilakukan PT.INDOFOOD.  Penelitian ini mengangkat tentang persoalan kreativitas iklan Indomie, Indomie adalah produk mie instant sudah ada sejak tahun 1980. Teori dan konsep penelitian yang digunakan adalah iklan, daya tarik iklan, media televisi dalam komunikasi massa, produk, merek (brand), dan juga kreativitas. Penelitian ini menggunakan penelitian kualitatif dengan metode studi kasus, analisis wacana, dan fenomologi. Penggumpulan data menggunakan wawancara dengan Raditya Cahya Buana sebagai Quality Control Noodle di PT.Indofood Semarang, studi dokumen dan studi literatur. Kesimpulan dari penelitian kreativitas iklan Indomie adalah dengan menampilkan iklan Indomie di televisi dengan menarik dan menghadirkan produk-produk Indomie yang baru.